The events of France in the year 1968 - Fatah Bahram Khdir (QALAAI ZANIST JOURNAL, 2024)
The events of 1968 form an important part of French history, It is to present a different picture of civil struggle for the achievement of a number of political, economic and social goals The events began with demonstrations by students at the University of Paris, and after spreading to other classes such as workers and women joined the demonstrators They had their own demands and the common interest brought them all to the streets, There were a number of internal and external factors that motivated the demonstrators. In several other discussions, several other parties such as the situation of the government, the slogans of the demonstrators, which is why we can read the situation in France at the time, events are a living example to discuss the role of the university in political, economic and social issues.